Survey of wind ensemble repertoire with double bass - Yang, Sungmo (My University, 2024)
The study of the use of the double bass in wind ensemble literature is limited. The double bass itself is a unique color instrument in wind bands, sometimes doubling with either the low brass section or low woodwind instruments, and in more recent repertoire often performing independent parts. Sometimes, wind band composers and conductors lack significant experience with string and especially, double bass technique. This project will analyze and explore various challenging figures from the wind ensemble repertoire that can pose some unique technical challenges to the double bass player in the wind band. In this project, I aim to examine scores of music, define potential problems for the double bassist, and suggest solutions and techniques. I aim for this project to serve as a resource for both ensemble directors and bass students to address the technical issues found in this repertoire. The pedagogical value of these studies is that they provide techniques for the bass player to address unique technical and interpretive skills while playing with winds. Chapter I will include the purpose, procedures and limitations for the study. The bulk of the content for this project will be to create a searchable database website as well as video demonstration of the techniques found in the literature. For each excerpt, the database will include song title, composer, reference links, metronome marking, and key arranged in chronological sequence. Therefore, in Chapter II I will examine related literature and provide links to the database website that I have created for this project. Chapter III will provide a brief history of the double bass in the wind band. Chapter IV includes a selection of often performed wind band compositions with challenging excerpts and technical solutions. This chapter is intended to be used with the website. Chapter V will include recommendations for programming and auditions repertoire for double bass students and Band directors and a conclusion.
Keywords: Music; Wind Ensemble; Double Bass